Case Report : Upaya Penanganan Pasien Laki – Laki usia 64 Tahun dengan Recent STEMI Inferior - Muhammad Daniyal; Emelda Emelda (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
A 64-year-old male patient presented to the emergency department (ED) of RS Cut Meutia with complaints of left-sided chest pain radiating to both arms, which had been occurring for two days prior to his hospital admission. The chest pain was described as sharp, sudden, and progressively worsening, and it persisted without relief from positional changes. The pain intensity was rated as 9/10 and was accompanied by cold sweats and nausea. The patient had a history of type 2 diabetes mellitus for 15 years and had been on antidiabetic medications, although he could not recall the names of the medications. The patient was a smoker but had quit smoking upon being diagnosed with diabetes. Vital signs and general status were within normal limits upon examination. Local examination of the heart revealed a murmur on auscultation. Laboratory results showed anemia, leukocytosis, hyperglycemia, and hypercholesterolemia. Electrocardiography (EKG) indicated signs of inferior STEMI (ST-Elevation Myocardial Infarction). The patient was treated with furosemide 1 amp/12 hours, atorvastatin 1x20 mg, arixtra 1x0.25 mg, aspilet 1x8 mg, clopidogrel 1x75 mg, nitrokaf retard 2x2.5 mg, and bisoprolol 1x2 mg, along with non-pharmacological management, including three-way catheter insertion and oxygen therapy at 2-4 liters per minute. Acute Coronary Syndrome (ACS) carries a poor prognosis if not managed promptly and correctly. Understanding the appropriate management of ACS is crucial in preventing further myocardial occlusion and improving patient outcomes. Therefore, rapid and accurate intervention is vital in improving the prognosis for patients with ACS.